Editorial (Thematic Issue: “Cell-penetrating Peptides and Drug Delivery”) - Huang, Yongzhuo (Current Pharmaceutical Biotechnology, 2014)
In recent years biomacromolecular drugs including proteins and nucleic acids have been emerging among the most promising therapeutics and globally recognized as one of the most cutting-edge areas of drug research. However, the nature of strong hydrophilicity and high molecular weight creates a formidable barrier for the biomacromolecules to diffuse through the cell membrane. Therefore, along with rapid development of biodrugs, cell-penetrating peptides (CPP) have also been intensively studied for the application in enhanced intracellular delivery of protein and nucleic acid drugs. CPP has also been found very effective in overcoming various bio-barriers at tissue levels, for instance, blood-brain barrier, [1] skin, [2, 3] nasal mucosa, [4] intestinal walls, [5] and intratumoral penetration barrier [6]. Hence, the research focus has gradually shifted from intracellular delivery to in vivo delivery. In this special issue, we include eight review papers that provide a glimpse into the CPP-based drug delivery. David and Choi provide a brief outline of the potential mechanisms for CPP-mediated cellular uptake including endocytosis and non-endocytosis pathways. Often, the translocation involves more than one pathway, as a result of multiple mechanisms varying with the diversity of CPPs and their cargoes. More recently, scientists have started to think more about the in vivo profiles of CPPs. The nature of nonselective penetration of CPP usually causes wide bio-distribution and unwanted drug exposure. Therefore, the pharmacokinetics information must be taken into account for rational design of CPP-based drug delivery, of which Mier and his colleagues provide a summary about the targeting and biodistribution issues. In particular, they summarized the strategy of using targeting motifs to modify the CPPs for altering their bio-fate. They also proposed that “smart delivery platforms” would be a potential solution for achieving targeted delivery. He et al. provide a detailed review on intelligent liposomal systems for targeted tumor delivery by employing the activatable CPP strategy. The activation is specifically triggered by the tumor-associated factors (e.g. low pH, proteases) or external stimuli (e.g. UV or exogenous agents). Of note, blood-brain barrier represents one of the most difficult challenges against effective drug delivery to the central nervous system, and Chen and his colleagues describe the promising CPP-based brain delivery techniques, in which CPPs play an important role in overcoming the formidable barrier. Topical application of CPP may benefit from its local action, because of limiting the unwanted wide drug distribution. Huang and Moon et al. give discussion on the transdermal and nasal delivery mediated by CPPs. Wang and He et al. outline the application of CPP-assisted oral insulin delivery. Due to charge interaction, conjugation of insulin with CPP still remains a problem, and they proposed a proper selection of linker would be helpful. Sun et al. pay attention to vaccine delivery. They mainly discuss the noninvasive vaccination based on CPP-mediated delivery including protein, peptide and DNA vaccines. Last but not least, Lee and his colleagues focus on an interesting topic of CPP-mediated delivery by non-covalent forms, which is featured by its ease to produce and use, and versatility to various types of cargos without the need of custom-tailored conjugation processes, compared to the chemical method. Growing understanding of the molecular mechanisms has promoted CPP’s application in pharmacotherapy against many diseases. Prospects for clinical translation of CPP-based therapy have emerged, and some clinical trials have been well underway [7]. Therefore, we believe such a featured topic of “Cell-penetrating Peptides and Drug Delivery” should be of great interest to the pharmaceutical community, as well as to colleagues in a broad biomedical field.